Minorities, Women, and Radicals in the Discipline of Economics - Scheiding, Thomas (Advances in Social Sciences Research Journal, 2024)
The discipline of economics is informally managed in the United States by the American Economic Association (AEA). The AEA’s management of the economics community however was challenged starting in the 1960s by blacks, women, and radicals. Blacks, women, and radical economists each adopted a different strategy towards achieving greater empowerment in the discipline. Black economists created the Caucus of Black Economists and participated in the AEA’s Committee on the Status of Minority Groups in the Economics Profession to encourage that steps be taken towards affirmative action and create a space for the publication of black economic research. Women economists participated in the AEA’s Committee for the Status of Women in the Economics Profession in 1971 to document the number of women in the economics profession, create a network of women economists and those supporting their work, and publish a newsletter containing statistics on representation within the profession and a listing of job openings and candidate availability. Radical economists created the Union for Radical Political Economics in 1968 to serve as a scholarly home for those holding non-mainstream beliefs and undertake the publication of a research journal, and sought some degree of solace from the AEA’s Committee on Political Discrimination. In the documentation of the different approaches taken by these groups, it becomes clear that there is no optimal inclusion strategy and that the barriers to being a recognized economist remain 50 years later.